Perancangan Komponen Modular untuk Pembentukan Spesifikasi dan Harga Sepeda OEM di PT X - Andrew Stephen; Tanti Octavia (Jurnal Titra, 2021)
PT X is a bicycle manufacturing industry that develops, manufactures and sells bicycles to several countries around the world. One of the marketing channels carried out by was OEM. The problem faced by the OEM Sales is the complexity of the work process in making specifications for bicycle components and the costing process. This complexity occurs due to the demand for customizable bicycle specifications from many customers which results in increased variations in the use of bicycle components. The purpose of this research is to design a modular component as a tool for making component specifications and bicycle prices that have the same use of components from different bicycle criteria. The research method was carried out qualitatively and quantitatively. The results obtained from the research are the process complexity of making specifications for bicycle components and the costing process were reduced. The main conclusion that can be drawn is the design of the modular components as a prototype program to facilitate the process of making component specifications and the costing process resulting in reducement of components usage on different bicycle criteria.